Argonaute-dependent small RNAs derived from single-stranded, non-structured precursors - Chak, Li-Ling; Okamura, Katsutomo (Frontiers in Genetics, 2014)
A general feature of Argonaute-dependent small RNAs is their base-paired precursor structures, and precursor duplex structures are often required for confident annotation of miRNA genes. However, this rule has been broken by discoveries of functional small RNA species whose precursors lack a predictable double-stranded (ds-) RNA structure, arguing that duplex structures are not prerequisite for small RNA loading to Argonautes. The biological significance of single-stranded (ss-) RNA loading has been recognized particularly in systems where active small RNA amplification mechanisms are involved, because even a small amount of RNA molecules can trigger the production of abundant RNA species leading to profound biological effects. However, even in the absence of small RNA amplification mechanisms, recent studies have demonstrated that potent gene silencing can be achieved using chemically modified synthetic ssRNAs that are resistant to RNases in mice. Therefore, such ssRNA-mediated gene regulation may have broader roles than previously recognized, and the findings have opened the door for further research to optimize the design of ss-siRNAs toward future pharmaceutical and biomedical applications of gene silencing technologies. In this review, we will summarize studies about endogenous ssRNA species that are bound by Argonaute proteins and how ssRNA precursors are recognized by various small RNA pathways.